Theory of light sail acceleration by intense lasers: an overview. (1st April 2014) - Macchi, Andrea
Abstract A short overview of the theory of acceleration of thin foils driven by the radiation pressure of superintense lasers is presented. A simple criterion for radiation pressure dominance at intensities around <alternatives><inline-graphic xlink:href="ark:/27927/pgj449hnfv" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> <![CDATA[$5 \times 10^{20}\ \mbox{W cm}^{-2}$]]> </alternatives> is given, and the possibility for fast energy gain in the relativistic regime is discussed.